1971
DOI: 10.2307/1955050
|View full text |Cite
|
Sign up to set email alerts
|

The Ecology of Peasant Communism in India

Abstract: The purpose of this article is to investigate the agrarian base of Indian communism through the use of statistical data and techniques in which the Communist vote over three general elections since 1957 is correlated with 35 largely socio-economic variables taken from Indian census data. The results indicate that two of these variables—landlessness in densely populated areas—explain a significant percentage of the variance in the Indian Communist vote. It is further suggested on the basis of statistical data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1971
1971
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Such studies commonly employ ecological or correlational methods that associate certain party types with underlying social structural variables. Lipset (1960) and Lipset and Rokkan's (1967) pioneering crossnational studies of parties showed strong correlations between conservative, democratic, or communist parties and dominant social cleavages such as income and religion (see also Dogan [1967], Linz [1966], and Zagoria [1971] for important empirical studies in this tradition). 6 The implicit neglect of the strategies and tactics of parties in a theory of party ascendancy is not simply a feature of the "pluralist" paradigm.…”
Section: Parties As Representations: the Correlational Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such studies commonly employ ecological or correlational methods that associate certain party types with underlying social structural variables. Lipset (1960) and Lipset and Rokkan's (1967) pioneering crossnational studies of parties showed strong correlations between conservative, democratic, or communist parties and dominant social cleavages such as income and religion (see also Dogan [1967], Linz [1966], and Zagoria [1971] for important empirical studies in this tradition). 6 The implicit neglect of the strategies and tactics of parties in a theory of party ascendancy is not simply a feature of the "pluralist" paradigm.…”
Section: Parties As Representations: the Correlational Methodsmentioning
confidence: 99%
“…The hypothesis that landlessness and high population density together explain a proclivity for radicalism (Zagoria 1971) is supported by the fact that most of the rebellions took place in two districts that shared a comparatively high man-to-land ratio. Moreover, wetland cultivation was a greater part of cultivation in south, compared with north, Malabar.…”
Section: The Structural Argument On Keralan Exceptionalism Reconsideredmentioning
confidence: 99%
See 1 more Smart Citation
“…The asset-poor/landless people are economically poor and therefore they tend to face problems getting organized (Chambers, 1983;Zagoria, 1971) -problems that are not absolutely insuperable, however (see below). It may be counter-argued that it is the poorest and the most-asset poor who are more rebellious for, to paraphrase Marx, they have nothing to lose but their chains.…”
Section: Figure 1 the Green Revolution And Land Productivity In Indiamentioning
confidence: 99%
“…NOTES 1. Modernization theorists argue that unequal land tenure patterns are related to political instability, particularly in rural, agricultural nations such as Honduras (Huntington, 1968;Moore, 1966;Kautsky, 1972;Zagoria, 1971;Russett, 1964), According to the IDB (1980-1981: 284, 400), 64% of the Honduran population is rural and 60% of Hondurans are illiterate; the Honduran GDP per capita of $639 is the third lowest in Latin America. For some newer, more complex theoretical views on the role of peasants in revolutionary movements, see Skocpol (1979).…”
Section: Journal Of Interamerican Studies and World Affairsmentioning
confidence: 99%